Compreendendo o sofrimento decorrente do trabalho nos motoboys de Fortaleza-CE - Gondim, Andressa Alencar (2009)
Contemporaneously, motorcycle delivery workers – also known as motoboys – have become popular due to their capacity of accomplishing tasks in a short period of time. Nonetheless, because of the risks the motoboys accept to take, they have been labeled as irresponsible riders by drivers and pedestrians. Hence considering that this group is formed by subcontracted workers who have to perform their job under dangerous circumstances, the present study aimed to research the link between the labor precarization experienced by the motoboys and the accident/violence risks they’re subject to. Their strategies to remain employed as well as the consequences of this relation were also discussed. Semi-structured interviews were undertaken with five motoboys from Fortaleza-CE, adopting the qualitative paradigm. The interviews were analyzed using thematic content analysis, methodology through which we came to understand that the job demands are directly related to the risks the motoboys are subject to on a regular basis. Since they need to optimize their time, trying to perform as much tasks as they can, in the shortest period of time possible, it turns out that they work under pressure and eventually violate traffic laws. The fact that they have no stable salary and that their income is proportional to their production is also another factor that increases the potential risks of work accidents. Urban violence is another important risk element against the motoboys, causing them to fear their work and forcing them to adopt defense strategies to remain on the job.